(untitled) (CIPEEX, 2026)
The growing recognition of mental health as a pressing societal concern, combined with the expansion of Integrative and Complementary Practices in Health (ICPH) within the Brazilian Unified Health System (SUS)—particularly in Primary Health Care (PHC)—has expanded the scope of biomedical professionals’ involvement in mental health care. This study aims to examine the integration of Biomedicine into complementary therapies for mental disorders, considering current regulations and the impacts reported by both patients and health professionals. An integrative literature review was conducted with a qualitative, descriptive, and exploratory approach. The review included articles published between 2019 and 2025, retrieved from databases such as SciELO, PubMed, LILACS, VHL, and the CAPES journal portal, as well as institutional documents, including the National Policy on Integrative and Complementary Practices in Health (PNPIC). Findings indicate that the incorporation of Biomedicine into complementary therapies, particularly acupuncture and phytotherapy, has yielded promising outcomes in the management of mental disorders by fostering a multidisciplinary care model. In conclusion, the integration of Biomedicine into complementary therapies plays a critical role in enhancing treatment effectiveness for mental disorders. This holistic and personalized approach contributes to sustainable and transformative outcomes for patients.